Measurement of lacrimal punctum using spectralis domain anterior optical coherence tomography. Issue 7 (28th December 2016) - Sung, Youngje; Park, Jong Seo; Lew, Helen
Abstract: Purpose: Anterior segment optical coherence tomography (AS‐OCT) was used to image the lacrimal punctum and establish normal punctal parameters including the tear volume inside the punctum. Methods: This study included totally 67 eyes from 38 normal subjects. Punctal parameters and tear meniscus height (TMH) were measured using spectralis OCT anterior‐segment scans. Outer punctal diameter (OPD), punctal depth, tear well diameter (TWD), tear well depth, punctal reserve (PR) and lower eyelid TMH were assessed. Authors defined a 'tear well' as a pool of standing tears in the punctum. Punctal reserve was defined as the difference between punctal depth and tear well depth. Results: Outer punctal diameter was 614.6 ± 195.6  μ m, the punctal depth was 545.8 ± 270.1  μ m, TWD was 229.9 ± 133.8  μ m, the tear well depth was 434.9 ± 247.8  μ m, the PR was 110.9 ± 72.9  μ m, the PR ratio was 0.20 ± 0.17, and the TMH was 222.9 ± 88.8  μ m. The punctal depth decreased significantly according to the patient's age (correlation coefficient = −0.352, respectively). Conclusion: AS‐OCT is useful for improving anatomical understanding of the lacrimal punctal structure. Quantitative punctum and tear well measurements were correlated with TMH.